Cytoplasmic HDAC4 recovers synaptic function in the 3×Tg mouse model of Alzheimer's disease. Issue 1 (15th November 2022) - Colussi, Claudia; Aceto, Giuseppe; Ripoli, Cristian; Bertozzi, Alessia; Li Puma, Domenica Donatella; Paccosi, Elena; D'Ascenzo, Marcello; Grassi, Claudio
Abstract: Aims: Early dysfunction in Alzheimer's disease (AD) is characterised by alterations of synapse structure and function leading to dysmorphic neurites, decreased spine density, impaired synaptic plasticity and cognitive deficits. The class II member HDAC4, which recently emerged as a crucial factor in shaping synaptic plasticity and memory, was found to be altered in AD. We investigated how the modulation of HDAC4 may contribute to counteracting AD pathogenesis. Methods: Using a cytoplasmic HDAC4 mutant (HDAC4 SD ), we studied the recovery of synaptic function in hippocampal tissue and primary neurons from the triple‐transgenic mouse model of AD (3×Tg‐AD). Results: Here, we report that in wild‐type mice, HDAC4 is localised at synapses and interacts with postsynaptic proteins, whereas in the 3×Tg‐AD, it undergoes nuclear import, reducing its interaction with synaptic proteins. Of note, HDAC4 delocalisation was induced by both amyloid‐β and tau accumulation. Overexpression of the HDAC4 SD mutant in CA1 pyramidal neurons of organotypic hippocampal slices obtained from 3×Tg‐AD mice increased dendritic length and promoted the enrichment of N‐cadherin, GluA1, PSD95 and CaMKII proteins at the synaptic level compared with AD neurons transfected with the empty vector. Moreover, HDAC4 overexpression recovered the level of SUMO2/3ylation of PSD95 in AD hippocampal tissue, and in AD organotypic hippocampal slices, the HDAC4 SD rescued spine density and synaptic transmission. Conclusions: These results highlight a new role of cytoplasmic HDAC4 in providing a structural and enzymatic regulation of postsynaptic proteins. Our findings suggest that controlling HDAC4 localisation may represent a promising strategy to rescue synaptic function in AD, potentially leading to memory improvement. Abstract : (A) Under physiological conditions, HDAC4 is localised at the dendritic spines and positively controls synaptic proteins by SUMOylation and by providing a scaffold for proper membrane localisation and function, thus favouring spine formation and stabilisation. (B) In Alzheimer's disease (AD) neurons, Aβ‐ and tau‐dependent mechanisms decrease HDAC4 localisation at synapses contributing to synaptic protein dysfunction and impaired synaptic transmission. Overexpression of a cytoplasm‐restricted HDAC4 mutant in AD neurons recovers synaptic protein localisation, dendritic spine density and synaptic transmission.